ICD-10 Classification in the Practice of Emergency Medical Teams: New Insights - Krzysztof M. Mitura; Jadwiga Snarska; Daniel Celiński; Dominik Maślach; Piotr K. Leszczyński; Aneta Binkowska; Leszek Szpakowski; Sławomir D. Szajda (Emergency Medicine International)
The role of the emergency medical system is to provide assistance to every person in a state in the event of a sudden threat to health and life. Emergency medical teams (EMTs) are an important element of this system, making diagnoses based on the International Classification of Diseases (ICD-10). The study was aimed at analysing the causes of EMT intervention based on groups of diagnoses codified according to the ICD-10. The analysis was based on data from 116,278 EMT interventions in central-eastern Poland in 2017-2019. The research showed that EMT most often made diagnoses based on groups of ICD-10 codes: R00-R99-Symptoms, signs, and abnormal clinical and laboratory findings, not elsewhere classified (39.11%); S00-T98-Injury, poisoning, and certain other consequences of external causes (18.23%); and I00-I99-Diseases of the circulatory system (15.57%). The analysis of the obtained results showed statistically significant differences (p<0.0001) regarding the area of intervention (urban, rural), sex, age of the patient, and the method of completion of the activities by EMTs in relation to the group of ICD-10 diagnoses for the diagnosis. The conducted study showed the actual reasons for EMT calls. The use of the ICD-10 classification has practical application in EMTs, as it enables the identification of a disease or health problem.